Taxonomic diversity and similarity of small mammal community in closed and open habitats - Siti Mariam, Binti Jamaluddin. (Universiti Malaysia Sarawak (UNIMAS), 2011)
A study of non-volant small mammal community in the forest of Sama Jaya Nature Reserve (closed habitat) and Kubah National Park (open habitat) was conducted for two different sampling periods: 12th May 2008 until 23rd September 2008 and 4th Februaury 2009 until 29th May 2009, respectively. Mark-recapture technique with trapping grid design was applied for this study.